Transforming Growth Factor Betal and Beta2 Induce Down-Modulation of Thrombomodulin in Human Umbilical Vein Endothelial Cells - Ohji, Taro; Urano, Hajime; Shirahata, Akira; Yamagishi, Minoru; Higashi, Ken; Gotoh, Sadao; Karasaki, Yuji (Thrombosis and Haemostasis, 1995)
To investigate the effects of transforming growth factor-betas (TGF-βs) on endothelial anticoagulant activity, we assayed thrombomodulin (TM) activity and antigen levels of human umbilical vein endothelial cells (HUVECs) incubated with TGF-βs in vitro. TGF-β1 suppressed surface TM activity and surface TM antigen levels maximally 12 h after incubation in dose-dependent manners. TGF-β2 was almost equipotent with TGF-β1 for the suppression of them. Both TGF-βs suppressed total TM antigen level in HUVECs, and the time course of the suppression was similar to that of the cell surface TM antigen level. The maximal reductions of TM mRNA levels by TGF-βs were observed at several hours ahead of those observed in both surface and total TM antigen levels, suggesting that the TGF-β-mediated suppression of TM antigen of HUVECs is primarily regulated at the TM mRNA level. Our present work suggests that the down-modulation of TM level induced by TGF-βs in HUVECs contributes in vivo to promoting the thrombogenesis either at the sites of injury of vessel walls, such as atherosclerotic lesions where TGF-β1 is released from platelets, smooth muscle cells and monocytes, or at neovascular walls in tumors secreting TGF-β2.